2013
DOI: 10.1002/grl.50909
|View full text |Cite
|
Sign up to set email alerts
|

Phase Space Density matching of relativistic electrons using the Van Allen Probes: REPT results

Abstract: [1] Phase Space Density (PSD) matching can be used to identify the presence of nonadiabatic processes, evaluate accuracy of magnetic field models, or to cross-calibrate instruments. Calculating PSD in adiabatic invariant coordinates requires a global specification of the magnetic field. For a well specified global magnetic field, nonadiabatic processes or inadequate cross calibration will give a poor PSD match. We have calculated PSD( , K) for both Van Allen Probes using a range of models and compare these PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…It is worth noting that both of these studies were limited to geosynchronous orbit, and so we might not expect the results to be generally applicable. Indeed, Morley et al () found that T96 better reproduced the magnetic field magnitude during the storm recovery phase that they studied, even though TS04 gave better results for phase space density matching.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that both of these studies were limited to geosynchronous orbit, and so we might not expect the results to be generally applicable. Indeed, Morley et al () found that T96 better reproduced the magnetic field magnitude during the storm recovery phase that they studied, even though TS04 gave better results for phase space density matching.…”
Section: Discussionmentioning
confidence: 99%
“…The configuration and strength of the geomagnetic field is a major controlling factor for energetic charged particle dynamics in the magnetosphere, including the dynamics of radiation belt electrons (e.g., Roederer & Zhang, ), ring current ions (e.g., Zaharia et al, ), cosmic rays, and solar energetic particle events (e.g., Desorgher et al, , Kress et al, ). For studies requiring magnetic conjugacy between satellites (e.g., Friedel et al, ; Morley et al, ) or between satellites and ground‐based instrumentation (e.g., Hones et al, ; Ge et al, ), the global morphology and mapping of magnetic field lines is crucial (e.g., Pulkkinen & Tsyganenko, ). Data‐based modeling of the external geomagnetic field has a long history of development in space physics (see Tsyganenko, , and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in the solar wind and geomagnetic parameters produce a sudden drop in the magnetopause position and the location of the last closed drift shell (LCDS) on 17 March, see Figures i and j. Note the LCDS is determined for 90° equatorial pitch angle electrons in the Tsyganenko and Sitnov () magnetic field model using the LANLmax and LANLstar algorithms (Yu et al, ) from the LANL* neural network (Morley et al, ). However, during the storm time interval on 17 and 18 March, the LCDS is obtained from the full calculation at a second adiabatic invariant of K = 0.05 G 1/2 Re using the LANLGeoMag software library (Henderson et al, ).…”
Section: The March 2013 and 2015 Geomagnetic Stormsmentioning
confidence: 99%
“…μ , K, and L * are the first, second, and third adiabatic invariants, respectively. For the relativistic electrons of a specified energy ( E ), their three adiabatic invariants and phase space density (f) are expressed as [ Kim and Chan , ; Chen et al , ; Morley et al , ; Reeves et al , ] follows: μ=E()E+2E02BE0sin2α K=truetrue∫sssnBmB()snormalds L*=2πMΦRE f(),,μKL*=3.325×10prefix−11j(),,EαrE()E+2E0 …”
Section: Relativistic Electron Loss During a Sscmentioning
confidence: 99%